Salbutamol attenuates arrhythmogenic effect of aminophylline in a hPSC-derived cardiac model - Kabanov, Daniil; Vrana Klimovic, Simon; Beckerová, Deborah; Molcan, Martin; Scurek, Martin; Brat, Kristian; Bebarova, Marketa; Rotrekl, Vladimir; Pribyl, Jan; Pesl, Martin (Scientific reports, 2024)
The combination of aminophylline and salbutamol is frequently used in clinical practice in the treatment of obstructive lung diseases. While the side effects (including arrhythmias) of the individual bronchodilator drugs were well described previously, the side effects of combined treatment are almost unknown. We aimed to study the arrhythmogenic potential of combined aminophylline and salbutamol treatment in vitro. For this purpose, we used the established atomic force microscopy (AFM) model coupled with cardiac organoids derived from human pluripotent stem cells (hPSC-CMs). We focused on the chronotropic, inotropic, and arrhythmogenic effects of salbutamol alone and aminophylline and salbutamol combined treatment. We used a method based on heart rate/beat rate variability (HRV/BRV) analysis to detect arrhythmic events in the hPSC-CM based AFM recordings. Salbutamol and aminophylline had a synergistic chronotropic and inotropic effect compared to the effects of monotherapy. Our main finding was that salbutamol reduced the arrhythmogenic effect of aminophylline, most likely mediated by endothelial nitric oxide synthase activated by beta-2 adrenergic receptors. These findings were replicated and confirmed using hPSC-CM derived from two cell lines (CCTL4 and CCTL12). Data suggest that salbutamol as an add-on therapy may not only deliver a bronchodilator effect but also increase the cardiovascular safety of aminophylline, as salbutamol reduces its arrhythmogenic potential.
Keywords: albuterol; aminofylin; Cell Line; Cardiomyocytes; Biomechanical properties; Pluripotent Stem Cells; bronchodilatancia; Heart Rate; Salbutamol; Albuterol; Drug cardiotoxicity; srdeční arytmie; srdeční frekvence; Microscopy, Atomic Force; Pulmonary drug screening; Arrhythmias, Cardiac; Atomic force microscopy, iPSC; pluripotentní kmenové buňky; mikroskopie atomárních sil; Arrhythmogenic effects; kardiomyocyty; lidé; Humans; Bronchodilator Agents; Myocytes, Cardiac; buněčné linie; Aminophylline; HESC